The present verb related to the Noon of emphasis and feminine Noon: Phonetic Study - Ibrahim, Islam Mahmoud (Journal of Arabic Language Sciences and Literature, 2022)
The study discussed the present verb related to the: Noon of emphasis and feminine Noon; where the subject of the current study framed many questions among linguists regarding the causation of the parsing present-tense verb with A Fatha when connected to the Noon of emphasis, and with A Sukoon when connected to the feminine Noon in all parsing cases: nominative, accusative, and dative. the study relies on linguistic views on the subject, both ancient and modern. the study also relied on modern audio efforts as a starting point for its presentation, analysis and conclusions.
Keywords: Present Verb; Strong form of Noon of Emphasis; Light form of Noon of Emphasis; Vowel Hiatus Feminine Noon